Muscle synergy structure using different strategies in human standing-up motion. (17th January 2017) - Yang, Ningjia; An, Qi; Yamakawa, Hiroshi; Tamura, Yusuke; Yamashita, Atsushi; Asama, Hajime
Graphical Abstract: Abstract: Standing-up motion is an important daily activity. It has been known that humans can employ different strategies to stand up from a chair, but it was not clear how people control their redundant muscles to achieve different strategies. This study employs the concept of muscle synergy which suggests that humans utilize the small number of modules (called muscle synergy) to generate the movements. This study uses two approaches to understand how humans generate different movements. Firstly, measurement experiment was performed to investigate the muscle synergy structure during different strategies. Next, the finding from the measurement experiment is validated through the forward dynamic simulation using our developed neuromusculoskeletal model. Both of our results from simulation study and measurement experiment showed that four muscle synergies could generate standing-up motion. However, they adaptively changed the start time of a certain synergy to achieve different strategies.